Prospect Theory and Travel Behaviour: a Personal Reflection Based on a Seminar - Wee, Bert van (European Journal of Transport and Infrastructure Research, 2010)
This paper is the final paper of a special issue on Prospect Theory (PT) and its applications in travel behaviour research. It is largely (but not exclusively) based on discussions held during a seminar that took place on the 8th of October 2009. The paper presents some personal reflections based on the discussion subjects on the use of PT in the area of travel behaviour research, clustered by the position of PT as a theory, applications of PT, future research, and relevance for policy making. The most important conclusion of the papers are firstly that PT, in addition to other theories like Utility Theory (UT), can help to improve our understanding of choices in the area of travel behaviour. The concepts of loss aversion and reference points are especially useful. A second important conclusion is that PT is not the only theory challenging UT. For example Regret Theory and the concept of Bounded Rationality also challenge PT. In addition, some of the premises of PT, at least the importance of some reference points, are not exclusively the domain of PT, but also that of other theories, including UT. Thirdly, it is important to realize that critics of Utility Theory (UT) as it is used in specific studies related to travel behaviour are not necessarily critics of UT in general. Fourth, it seems better to focus on the distinguishing premises of PT than on the theory as a fully fledged alternative to UT. A fifth outcome is that PT can be used both to increase our understanding of travel behaviour, as well as for the evaluation of the outcomes of models. A final outcome is that there is no need to choose a theory before collecting the data.